Evaluasi Penggunaan Media Audiovisual Dalam Pembelajaran IPAS Di SD Negri 32 Kota Bengkulu - Nipi Mariska; Nurhalizha; Windi; Peteri Koriyati (JPT : Jurnal Pendidikan Tematik, 2024)
Evaluation of the use of audiovisual media in Natural and Social Sciences (IPAS) learning in Elementary Schools is a systematic process to measure the effectiveness and benefits of these media in supporting the learning process. Education aims to develop students' potential through learning that enhances intelligence, character, and relevant competencies, where success is measured by learning outcomes influenced by the methods and media used by educators. Audiovisual media, which combines images and sound, is an innovative solution in delivering material systematically and interestingly, increasing student engagement and understanding, and can even replace the role of teachers when direct instruction is constrained. This evaluation focuses on measuring student engagement, understanding, and learning outcomes using audiovisual media as a teaching aid in IPAS learning, aiming to ensure improved learning quality and optimal student competency achievement.